Development Of Higher Order Thinking Skills (Hots) Questions On Leaf Folding Material For Culinary Vocational School Students Phase E - Shofi Ulfa Rosyida; Febriani Lukitasari; Sri Handajani; Fitri Komala Sari (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
Learning evaluation in culinary basics subject on leaf folding material at vocational high school is still dominated by questions that measure low-level thinking skills, so that students' critical thinking skills have not developed optimally. This research aims to develop and test the quality of This study aims to develop and test the quality of Higher Order Thinking Skills (HOTS) questions in category C3-C5 on leaf folding material for vocational high school culinary students in Phase E. The research method used is Research and Development (R&D) with the ADDIE model limited to the development stage. The product developed consists of 30 multiple-choice questions based on HOTS. The content validity of the instrument was conducted through expert judgment by three validators consisting of subject matter experts and evaluation experts, with a suitability percentage of 98.6% and classified as very suitable. Empirical testing was conducted on 32 students in the 10th grade of the Culinary Skills Program. Of the 30 questions tested, 22 were declared valid and 8 were not valid. The reliability test results showed a coefficient of 0.825, which is in the very high category. The difficulty level analysis showed that the questions were in the moderate category, the discriminating power was in the fair to good category, and the distractors functioned effectively. Thus, the HOTS questions that were developed were declared suitable for use as learning evaluation tool for leaf folding material.